Biosecurity and Biological Risk Management for Livestock Enterprises - Matt Hersom; Max Irsik; Todd Thrift (EDIS)
AN-194, a 6-page fact sheet by Matt Hersom, Max Irsik, and Todd Thrift, describes biosecurity and biological risk management practices, basic biosecurity and BRM management practices, disease transmission routes, enterprise security, reasons to have a BRM plan, and biosecurity best management practices. Includes resource list. Published by the UF Department of Animal Sciences, March 2008.